2022
DOI: 10.7860/jcdr/2022/51153.15955
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Incisional Negative Pressure Wound Therapy Following Incisional Hernia RepairA Randomised Controlled Trial

Abstract: Introduction: Incisional hernia is one of the common complications following abdominal surgery in patients undergoing laparotomy. Various surgical procedures are performed by creating a potential space and placing a foreign body (mesh), which may render the wound susceptible for many postoperative complications. It is clinically important to evaluate the efficacy of Incisional Negative Pressure Wound Therapy (INPWT) in reducing wound complications. Aim: To compare the efficacy of INPWT dressing with tradition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The use of standard surgical dressing and emergency colorectal surgery were associated with a higher risk of developing SSI. In the results of Mondal et al, the group that received NPWT also had fewer patients developing SSI than the control group (19). However, in this study, where participants were intervened due to presenting incisional hernia, all documented SSIs were considered superficial.…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations
“…The use of standard surgical dressing and emergency colorectal surgery were associated with a higher risk of developing SSI. In the results of Mondal et al, the group that received NPWT also had fewer patients developing SSI than the control group (19). However, in this study, where participants were intervened due to presenting incisional hernia, all documented SSIs were considered superficial.…”
Section: Discussionmentioning
confidence: 57%
“…Another of the conclusions found when analyzing the articles was the formation of seroma. Regarding this postoperative complication, Mondal et al and Chambers et al agree since both studies showed that the difference was not statistically significant between the two groups (19,25). In De Rooij et al study, during NPWT, the mastectomy wound surface was under external nominal negative pressure of 80 mmHg by the NPWT pump during seven days, and the results should point to a favorable effect on seroma formation.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…There are some limitations of this meta-analysis. First, most studies involved in this meta-analysis were retrospective and only two RCTs were included, which may introduce a selection bias in the process [ 46 ]. Second, the definition of SSO was different among articles.…”
Section: Discussionmentioning
confidence: 99%